Design Journeys through Complex Systems : practice tools for systemic design - Jones, Peter, ....-; Van Ael, Kristel, ....- (Amsterdam : BIS Publishers, 2022)
Design Journeys for Complex Systems is a designer's handbook to learn systemic design tools to engage stakeholder groups in collaborative design to address complex societal systems. Systemic design uses systems thinking and service design to address large-scale societal contexts and complex socio-technical systems. These are contexts characterized by social and technological complexity, high uncertainty, and often problematic outcomes. Using a tour guide metaphor, the book trains people's mindsets and provides tools for dealing with hyper complexity, to enable understanding of systemic problems, and to build capacity to collaborate in teams to produce action proposals.
Keywords: Systeemtheorie sociale wetenschappen